Smartphone‐coupled Electrochemical Analysis of Cellular Superoxide Anions Based on Mnx(PO4)y Monolayer Modified Porous Carbon. Issue 3 (29th November 2019) - Cai, Xuan; Gao, Qianmei; Zuo, Shaohua; Zhao, Hongli; Lan, Minbo
Abstract: Here we established a palm‐sized electrochemical sensor for the determination of cell‐released superoxide anions (O2 .− ) based on a self‐developed portable potentiostat (xenSTAT) which can perform fast analysis with visual real‐time data and customizable parameters. The xenSTAT was equipped with Bluetooth and USB interfaces, thus being able to be connected with both smartphones and computers for electrochemical analysis. A novel Nanozyme based on Mnx (PO4 )y monolayer modified porous carbon cubic was synthesized and used as functional material on the surface of working electrode. By using cyclic voltammetry (CV) and chronoamperometry, xenSTAT was demonstrated to exhibit satisfying sensitivity and excellent stability for real‐time monitoring of O2 .− released from cancer cells. With decreased cost, customizable development, small size and convenient usage, the xenSTAT described in this work could promote the commercialization and widespread of in‐house built electrochemical sensors for the monitoring of O2 .− in the future. Abstract :